Lentinan's effect on gut microbiota and inflammatory cytokines in 5-FU-induced mucositis mice - Xiaoxiao Zhang; Liang Wang; Asif Iqbal Khan; Ata Ur Rehman; Kavish Hasnain Khinsar; Yi Xin (AMB Express)
Abstract Chemotherapeutic therapies for cancer are frequently associated with cytotoxic side effects that can be harmful to human health, including the development of intestinal mucositis (IM). It mostly affects the gastrointestinal tract, causing ulceration, inflammation, and the formation of lesions in the colon. Surprisingly, despite the frequency of IM, therapeutic choices remain restricted. In our search for new intestinal mucositis therapies, we wanted to see how Lentinan (LT), derived from Lentinus edodes, would fare in mouse models of intestinal mucositis. To create the intestinal mucositis model in mice, we gave them intra-peritoneal doses of 5-fluorouracil (5-FU) (50 mg/kg) and then tested the effects of Lentinan on intestinal mucositis. This examination required constant monitoring of several factors, such as body weight fluctuations, food consumption, and diarrhea. In addition, we measured the levels of certain inflammatory cytokines (Tumour Necrosis Factor-alpha (TNF-α), Interleukin-1 (IL-1), Interleukin-6 (IL-6), and Interleukin-10 (IL-10), looked at the expression of tight junction proteins (Zonula Occludens-1(ZO-1), Claudin-1), measured mucin-2 levels, and looked into changes in the gut flora. In the mouse model of intestinal mucositis, our findings showed that LT effectively reduced weight loss, increased food intake, and relieved diarrhea. Concurrently, we saw a decrease in the expression of inflammatory cytokines such as TNF-α, IL-1, and IL-6, as well as a considerable increase in the concentration of IL-10. Furthermore, LT reduced intestinal mucositis by increasing the length and structural integrity of the colon. Furthermore, increased expression of tight junction proteins (ZO-1, Claudin-1), mucin-2, and an increase in the number of goblet cells all confirmed our previous findings. Notably, the makeup of beneficial bacteria in the stomach increased as well. Finally, our findings suggest that LT can effectively prevent 5-fluorouracil-induced intestinal mucositis in mice by improving immune function, restoring intestinal barrier integrity, and rebalancing gut microbial flora.